Virtual Communities of Practice for generations Z and Alpha: a systematic review of the main social networking sites used in formal education - Castiglione Alessio (Reports on Geodesy and Geoinformatics)
The use of social networking sites (SNSs) in teaching is of increasing importance, for it puts into question how what we have, until the digital revolution, understood formal education to be. The earliest social media came about and were developed parallel to generations Z and Alpha. This review analyzed at least 8 articles published between 2019 and 2023, found on the databases Web of Science and Scopus, and sorted into four categories of research cases focused on the main SNSs used in formal education. The selected studies show that Whatsapp, Twitter, Instagram, and TikTok can have a positive impact on student and teacher motivation, collaboration, and the reaching of learning objectives. Further, this paper brings to light the advantages that SNSs can bring to faculty’s professional development and to learning, in addition to their value as motivating resources and community-forming structures.